2009
DOI: 10.1666/08-064.1
|View full text |Cite
|
Sign up to set email alerts
|

Neoproterozoic microfossils from the northeastern margin of the East European Platform

Abstract: The Kel'tminskaya-1 borehole, drilled along the northeastern margin of the East European Platform (EEP), reveals some 3,600 m of Neoproterozoic sedimentary rocks, mostly confined to the subsurface. The upper 1,000 m of the drilled section correlates with late Ediacaran Redkino and Kotlin successions on the EEP, whereas the lowermost 2,000 m can be related to pre-Sturtian (Upper Riphean) deposits in the Ural Mountains. In between lies the Vychegda Formation, a 600 m siliciclastic succession that has no counterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 64 publications
3
66
0
Order By: Relevance
“…4 a-c,e), as well as forms not previously reported (Fig. 4d, f-j; see Vorob'eva et al, 2009). The Kel'tma microbiota also contains morphologically simple filamentous and coccoidal microfossils of broad stratigraphic range, including Chuaria circularis, Polytrichoides oligofilum, Polysphaeroides filiformis, Elatera binata, Glomovertella eniseica, Leiosphaeridia spp., Siphonophycus spp., and some unusual morphotypes, such as large multilayered stalks made up of carbonaceous cones nested inside one another (Fig.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…4 a-c,e), as well as forms not previously reported (Fig. 4d, f-j; see Vorob'eva et al, 2009). The Kel'tma microbiota also contains morphologically simple filamentous and coccoidal microfossils of broad stratigraphic range, including Chuaria circularis, Polytrichoides oligofilum, Polysphaeroides filiformis, Elatera binata, Glomovertella eniseica, Leiosphaeridia spp., Siphonophycus spp., and some unusual morphotypes, such as large multilayered stalks made up of carbonaceous cones nested inside one another (Fig.…”
supporting
confidence: 87%
“…Even when these factors have been taken into account, it is clear that the uppermost Vychegda assemblage contains forms not previously described from other localities. Nonetheless, it shares at least four morphospecies (Alicesphaeridium medusodieum, Cavaspina acuminata, Tanarium conoideum, and T. tuberosum) with ECAP assemblages in Australia, Siberia or both (Vorob'eva et al, 2009). The chief caveat in this interpretation is our limited understanding of microfossil assemblages in uppermost Cryogenian (post-Sturtian/preMarinoan) rocks.…”
Section: Discussionmentioning
confidence: 99%
“…These pair-wise comparisons indicate that Ediacaran acanthomorph assemblages are less similar to one another than are widely distributed Cambrian acritarch assemblages from a common biostratigraphic zone (Vorob'eva et al, 2009a). The relatively low similarity of Ediacaran acanthomorph assemblages across the present day Russian land mass could reflect age, environment or biogeographic provinciality.…”
Section: Biogeographic Distribution Of Ecap Acritarch Taxa-within Rumentioning
confidence: 85%
“…Relying on the best documented assemblage from central Siberia, that of the Khamaka Formation (Moczydłowska et al, 1993;Moczydłowska, 2005), we can quantify similarities across Russia using Sorensen's Quotient of Similarity (Q/S=100 x 2j/(a + b), where a and b are the number of taxa found in each assemblage and j equals the number of taxa in both assemblages; Vorob'eva et al, 2009a). In their discussion of the Ediacaran acanthomorph assemblage from the Vychegda Formation, northeastern Russia, Vorob'eva and coauthors found its composition to be more similar to that of the Khamaka assemblage than it was to contemporaneous assemblages from Australia or China.…”
Section: Biogeographic Distribution Of Ecap Acritarch Taxa-within Rumentioning
confidence: 99%
“…Most also bear one to many spinose or branched processes distributed across vesicle surfaces. LOEMs are minor components of lower Ediacaran successions, but increase dramatically in both abundance and diversity at higher stratigraphic levels (2,13). Where microfossils and carbon isotopic data are available for the same succession, LOEMs disappear within or just below an interval marked by a pronounced negative C-isotopic excursion tightly constrained by a 551 Ϯ 0.7 Ma U-Pb date near its top but only loosely bracketed from below by ca.…”
Section: Large Ediacaran Microfossils: Systematic Interpretationmentioning
confidence: 99%